KADAR VITAMIN C, MUTU FISIK, pH DAN MUTU ORGANOLEPTIK SIRUP ROSELLA (Hibiscus Sabdariffa, L) BERDASARKAN CARA EKSTRAKSI - Ummu Mukaromah; Sri Hetty Susetyorini; Siti Aminah (Universitas Muhammadiyah Semarang, 2010)
Rosella flower contains vitamin C that is 260-280 mg in 100 grams. Rosella can be processed into syrup, extracts of roselle can be done by heating or without heating. The purpose of this study was to determine the effect of extraction of the vitamin C content, physical quality, pH and organoleptic quality of roselle syrup. This research using completely randomized design with 2 treatment by extraction and 13 replicates. Analysis of vitamin C oksidimetri method, measurement of total dissolved solids using handrefraktometer, measurement of viscosity using viskosimeter, measurement of pH using a pH indicator. Results showed that vitamin C in fresh rosella flowers as much as 144 mg/100 grams, moisture content and pH of 73.415% fresh roselle 2. Extraction effect on vitamin C content rosella syrup because, but did not affect the physical quality of rosella syrup. Panelists favored from the extraction of roselle syrup by heating. Key words: roselle syrup, extract, vitamin C.